2015
DOI: 10.1097/bot.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Fixation of Supination External Rotation Type IV Equivalent Ankle Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“… 25 In other data, no significant difference was observed in postoperative maintenance of reduction between anatomical and trans-syndesmotic fixation. 22 The findings highlight the ability of posterior malleolar fracture fixation to be as good, if not superior, at achieving a postoperatively stable syndesmosis while avoiding the risk of malreduction. The promising results seen in terms of reduction and stability make this new fixation strategy a feasible alternative to the traditional trans-syndesmotic fixation and may render the use of the syndesmosis screw or suture-button unnecessary.…”
Section: Anatomical Approachmentioning
confidence: 79%
See 1 more Smart Citation
“… 25 In other data, no significant difference was observed in postoperative maintenance of reduction between anatomical and trans-syndesmotic fixation. 22 The findings highlight the ability of posterior malleolar fracture fixation to be as good, if not superior, at achieving a postoperatively stable syndesmosis while avoiding the risk of malreduction. The promising results seen in terms of reduction and stability make this new fixation strategy a feasible alternative to the traditional trans-syndesmotic fixation and may render the use of the syndesmosis screw or suture-button unnecessary.…”
Section: Anatomical Approachmentioning
confidence: 79%
“…One study where the anatomical approach was used to fix supination external rotation type IV ankle fractures demonstrated a significant decrease in syndesmosis malreduction rate from 33.3% to 7.4% compared with trans-syndesmotic fixation. 22 Primary repair of the deltoid ligament, a key stabilizer of the talus within the ankle mortise, effectively restores congruity of the mortise comparable with syndesmosis screw fixation. 23 , 30 In the assessment of ankle and syndesmotic rotational stability, a biomechanical cadaveric study has shown that combined repair of the PITFL and deltoid ligament restores equivalent stability in resisting external rotation forces compared with syndesmosis screw fixation, with the repaired deltoid ligament functioning as a medial checkrein.…”
Section: Anatomical Approachmentioning
confidence: 99%
“…have not yet been well established. Some studies have shown that repair of the ruptured ligament is beneficial and can produce satisfactory results [11,12,14,20]. By contrast, other studies showed repair of the deltoid ligament to be unnecessary [1,4,10,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, suture-anchor was widely used for patients treated with deltoid ligament repair (DLR) [9][10][11], and plaster casts were most often used in treatment without DLR. Previous studies had shown that transarticular external fixators might raplace the plaster casts well by offering the opportunity for self-healing of deltoid ligament and allowing early weight bearing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%